Pupil diameter reflects uncertainty in attentional selection during visual search - Geng, Joy J.; Blumenfeld, Zachary; Tyson, Terence L.; Minzenberg, Michael J. (Frontiers in Human Neuroscience, 2015)
Pupil diameter has long been used as a metric of cognitive processing. However, recent advances suggest that the cognitive sources of change in pupil size may reflect LC-NE function and the calculation of unexpected uncertainty in decision processes (Aston-Jones & Cohen, 2005b; Yu & Dayan, 2005). In the current experiments, we explored the role of uncertainty in attentional selection on task-evoked changes in pupil diameter during visual search. We found that task-evoked changes in pupil diameter were related to uncertainty during attentional selection as measured by reaction time and performance accuracy (Experiments 1-2). Control analyses demonstrated that the results are unlikely to be due to error monitoring or response uncertainty. Our results suggest that pupil diameter can be used as an implicit metric of uncertainty in ongoing attentional selection requiring effortful control processes.